Diabetes mellitus literacy in a regional community of a developed country: Diabetes literacy in rural community - Chen, Adelene; Chidarikire, Thelma; Sarswat, Drishti; Parissi, Cesidio; Nwose, Ezekiel Uba (Acta Biomedica Atenei Parmensis, 2019)
Summary. Background: Prevalence of diabetes mellitus (DM) is on the increase. Yet discrepancies exist in research reports regarding the level of knowledge of the disease in ‘rural versus metropolitan communities’, and ‘developed versus developing countries’. This study examines the level of general knowledge of diabetes among adult community members of a regional city of Australia, whether it is comparable to reports from low-mid income countries. Methods: The study was designed to be a cross-sectional day-time-population survey. Major shopping centres were chosen for convenience sampling of community’s daytime population. A total of 315 participants’ (154 males and 161 females) responses were received. Data were analysed using SPSS – 20 software to identify differences between sub-groups of age stratifications, educational status, gender and the participants assumed knowledgee. The participant’s average knowledge of diabetes symptoms and complications were also assessed. Results: The major finding is that the subgroup who claimed to know ‘very little’ showed equivalent knowledge levels with those who thought they had ‘considerable knowledge’. The females know more about diabetes management than males (P < 0.004); level of knowledge increased with educational status (p < 0.01). These observations were comparable with reports from developing countries. Conclusions: The limited knowledge of diabetes symptoms and complications in the population can be mitigating against early reporting of patients to diabetes clinics in the community. To ensure continuous decline in prevalence rates of diabetes and its complications, the ongoing efforts of diabetes awareness and educational programs need to be improved, particularly with regard to males and school children. (www.actabiomedica.it)